2021
DOI: 10.1002/gps.5650
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, mood, and cognitive performance in older adults with cognitive impairment during the first wave of COVID 19 in Argentina

Abstract: Background and Objectives In Argentina, government has established lockdown on 19 March 2020 to decrease SARS‐COV‐2 infection. The study aim was to understand how mandatory quarantine imposed due to COVID‐19 pandemic has affected quality of life, mood, and cognitive performance of older adults with cognitive impairment. Design Longitudinal descriptive–observational study. Participants Patients with cognitive impairment attending to online cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Another factor to consider was whether living alone during COVID-19 confinement was associated with a higher prevalence of depression. Although several studies have found a significant association between depression and living alone during the pandemic [ 42 , 58 ], others have shown otherwise [ 59 , 60 ]. Our results are in line with the second ones, showing no significant differences in GDS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor to consider was whether living alone during COVID-19 confinement was associated with a higher prevalence of depression. Although several studies have found a significant association between depression and living alone during the pandemic [ 42 , 58 ], others have shown otherwise [ 59 , 60 ]. Our results are in line with the second ones, showing no significant differences in GDS scores.…”
Section: Discussionmentioning
confidence: 99%
“…During the medium and long period of COVID-19 lockdown measures, all groups of neurological patients exhibited a significant decline in functional and cognitive status compared to the pre-COVID period. During the medium period (5 to 8 months), three out of four studies showed adverse effects of COVID-19 lockdown measures on attention [ 46 ], and on the overall patients’ cognitive status [ 48 , 49 ], except for Ref. [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the lack of social stimulation and pleasurable activities favored the onset of anxiety and depression, which, in turn, cognitively affected the progression of the disease [ 106 ]. During the first wave of COVID-19, together with a general cognitive decline, Aragón et al, 2022 [ 46 ] reported a worsening in selective attention tasks in four patients with subjective cognitive decline and forty-seven MCI participants. These tasks were appropriately designed by the authors for testing executive attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universidade Federal do Delta do Parnaíba (UFDPar), Parnaíba -PI 2. Universidade de Cuiabá (UNIC), Cuiabá -MT 3.…”
unclassified